Homo interreligiosus: Zur biographischen Verortung interreligiöser Prozesse bei Raimon Panikkar (1918-2010). Beiträge einer internationalen Fachtagung zu seinem 100. Geburtstag (2021)
The essays of this volume are mainly lectures given at the international conference held at the Center for Intercultural Theology and the Study of Religion at the University of Salzburg on the occasion of Raimon Panikkars 100th birthday. They look at the life and thought of this outstanding pioneer of interreligious dialogue - already by descendancy rooted in two cultures and religions (Europe and Asia, Christianity and Hinduism) - not only from theological, philosophical, religious studies and spiritual perspectives, but also from a biographical-personal view and investigate into the relevance and inspiration of his life and works for today.